2019
DOI: 10.1007/978-3-030-20618-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Understandability of a Hybrid Process Design Artifact Based on DCR Graphs

Abstract: Process design artifacts (e.g., process models, textual process descriptions and simulations) are increasingly used to provide input for requirements elicitation and to facilitate the design of business processes. To support the understandability of process models and make them accessible for end-users with different backgrounds, several hybrid representations combining different design artifacts have been proposed in the literature. This paper investigates the understandability of DCR-HR, a new hybrid process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Hybrid process representations are introduced in the literature in two contexts: (a) to designate hybrid languages (e.g., [14]) or (b) to describe hybrid process artifacts. While hybrid languages combine existing languages to enable a concise and precise representation of business processes, hybrid process artifacts combine two or more process artifacts overlapping in the description of some aspects of the business process [1]. The emergence of hybrid process artifacts is driven by three main motivations: (1) supporting the understandability of process models (cf., [1,2]), (2) enhancing the maintainability of process models (cf., [16]), and (3) improving the modeling of business processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid process representations are introduced in the literature in two contexts: (a) to designate hybrid languages (e.g., [14]) or (b) to describe hybrid process artifacts. While hybrid languages combine existing languages to enable a concise and precise representation of business processes, hybrid process artifacts combine two or more process artifacts overlapping in the description of some aspects of the business process [1]. The emergence of hybrid process artifacts is driven by three main motivations: (1) supporting the understandability of process models (cf., [1,2]), (2) enhancing the maintainability of process models (cf., [16]), and (3) improving the modeling of business processes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, process artifacts have been more and more integrated in the development of PAIS, leading to hybrid solutions that loosely combine different artifacts with the aim to support the design and comprehension of process models [2,3], especially those lying under the umbrella of the declarative paradigm [4][5][6][7][8][9]. Such hybrid solutions combine (graphical) process models with textual process specifications [6,8] and interactive simulations [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…The use of declarative languages results often in complex models, which are hard to interpret and maintain by humans. Comprehending the human cognitive processes impacting the understandability of process models, paves the way toward the adoption of modeling practices, enhancing the comprehension of declarative models and thus supporting their use for management purposes [4,5]. In the field of cognitive psychology, existing research has shown the limited capacity of the human working memory [6].…”
Section: Introductionmentioning
confidence: 99%
“…We design questions to reflect the use of process models in practice. Similar to [5,16,44], we formulate questions addressing: the presence and absence of constraints in the model, order of activities and validity of process executions. We make dichotomous questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation